RNA-Sequence Reveals the Regulatory Mechanism of miR-149 on Osteoblast Skeleton under Mechanical Tension - Yifan Wang; Guanyin Zhu; Fang Pei; Yigan Wang; Jun Liu; Caixia Lu; Zhihe Zhao (Stem Cells International)
Objective. Based on RNA-sequencing (RNA-seq), the regulation of miRNAs differentially expressed in dental, periodontal, and alveolar bone tissue of orthodontic tree shrews on osteoblast skeleton under tension was investigated. Methods. Tree shrews were used to construct orthodontic models. We used RNA-seq to identify differentially expressed miRNAs in periodontal tissues of the treatment group and control group tree shrews. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used for enrichment analysis. Human osteoblast MG63 was treated with 5000 U mechanical tension. Real-time quantitative polymerase chain reaction (RT-qPCR) detected the expression of miR-149 and ARFGAP with SH3 domain, Ankyrin repeat, and Ph domain 3 (ASAP3) mRNA. Western blot detected the protein levels of ASAP3, F-actin, osteogenic markers bone morphogenetic protein 2 (BMP2), and runt-related transcription factor 2 (RUNX2). Rhodamine phalloidin was used to observe the fluorescence intensity of F-actin. Validation of the targeting relationship between miR-149 and ASAP3 by dual luciferase reporter gene assay. Results. By performing miRNA-seq analysis on the dental and periodontal tissue of tree shrews in the treatment group and control group, we identified 51 upregulated miRNAs and 13 downregulated miRNAs. The expression of miR-149 in the dental and periodontal tissue of tree shrew and MG63 cells treated with mechanical tension was decreased, and miR-149 targeted ASAP3. Knockdown of ASAP3 inhibited the fluorescence intensity of F-actin in MG63 cells treated with 5000 U tension for 36 h, and overexpression of ASAP3 promoted the expression of F-actin and osteogenic markers BMP2 and RUNX2. Conclusions. These findings revealed that miR-149 could modulate osteoblast differentiation under orthodontics mechanical tension through targeting ASAP3.